Nanosuspension Formula of Curcuma xanthorriza Rhizome Dry Extract: Impact of Tween 80-PEG 400 Ratio - Arifin, Moch Futuchul; Shafira, Elza; Noviani, Yuslia; Desmiaty, Yesi; Okta, Fauzia Noprima (Sciences of Pharmacy, 2024)
Our previous research investigated nanosuspension using the ionic gelation method with a 2:1 ratio of chitosan to sodium tripolyphosphate (TPP) and 0.44% Curcuma xanthorriza rhizome extract. The results indicated an unstable nanosuspension with a particle size of 399.3 nm, a polydispersity index of 0.60, and an entrapment efficiency of 73.37%. This study aims to develop a nanosuspension using Tween 80-PEG 400 to improve the characteristics and dissolution at pH 6.8. Curcuma rhizome was macerated with 96% ethanol and dried using a spray dryer. The nanosuspension formulation was designed using a 22 factorial design with Tween 80 (0.1%-0.4%) and PEG 400 (0.1%-0.4%) as factors, and the formulation was analyzed using Minitab 18. The dissolution of the optimum formulation was tested. The best formulation, comprising 0.1% Tween 80 and 0.4% PEG 400, provided a spherical shape, a particle size of 111.26 nm, a polydispersity index of 0.27, a zeta potential of 30.77 mV, an entrapment efficiency of 84.30%, and a desirability value of 0.9058. The release of curcumin at pH 6.8 after 180 minutes was 37.85% ± 0.1375 with a DE180 of 83.60% ± 0.1457. The 22 factorial design proved effective for enhancing formulation attributes. Based on the result obtained, it can be concluded that the best formulation contains 0.1% Tween 80 and 0.4% PEG 400, with zero-order release kinetics and a diffusion mechanism.